Education, Ideology and Literature: Incidence of the Ecuadorian Literary Canon in the Curricular Guide - Rengifo Vásconez, Luis Alberto (2023)
The national curriculum has been evaluated and updated on several occasions to solve problems identified around student learning. Previously reduced to a study program, the curricular guide was converted into a guiding document for pedagogical management. However, it is still necessary to evaluate the issue of legitimated knowledge that is expressed through the curriculum. It is not enough to provide solutions to how the student learns but to critically analyze what aspects of the collective culture have been considered in the exercise of cultural transmission. This essay exposes the process through which orthodoxy is configured in the Ecuadorian literary field. For this, the ideological and discursive project consolidated in Ecuador’s two different historical periods is briefly analyzed. The school, as a reproductive agent of the fabric of discourses in circulation, can favor the conservation of the canon. On the other hand, the action of the ideological projection of the current curriculum maintains the reproduction of legitimized knowledge. The ideology of the Language and Literature curriculum is studied from two areas: the technical-administrative needs of the industrial economy and the negative treatment of the uses of the conflict that depoliticizes it.